IMPLEMENTATION OF SAMBAS REGENT REGULATION NUMBER 18 OF 2018 CONCERNING ENVIRONMENTAL PERMITS FOR GOLD MINING IN TEBING BATU VILLAGE - Nurkarima (Archipelago Journal of Southeast Asia Islamic Studies, 2024)
This research was motivated by the existence of a gold mining business managed by a group of communities in Tebing Batu Village, Sambas Regency. The mine has been established for a long time but some do not have environmental permits from either the Village Government or the District Government. Meanwhile, in Sambas Regency, there are laws and regulations governing environmental permits, namely Regent Regulation Number 18 of 2018 concerning Environmental Permits. The objectives of this study are twofold, namely: to determine the implementation of Regent Regulation Number 18 of 2018 concerning Environmental Permits for Gold Mining in Tebing Batu Village; and to assess the legal consequences of mining activities in Tebing Batu Village based on Sambas Regent Regulation Number 18 of 2018 concerning Environmental Permits. This research uses a descriptive method, namely research that uses an overview of the facts, nature, and relationships between the events studied. This type of research is qualitative which is field research. This research also includes empirical legal research that examines social issues in terms of laws and regulations, namely Sambas Regent Regulation No. 18 of 2018 concerning Environmental Permits. To obtain research data, researchers used interview and observation techniques. The findings of this study are that the implementation of Sambas Regent Regulation Number 18 of 2018 concerning Environmental Permits is still not optimal because there is a mining business that does not have a business license and is not yet required AMDAL where environmental permits are the initial instrument for issuing business permits. The legal consequence is that the mining business is actually not fit to operate because it does not have an environmental permit so that parties involved in the mining business can be subject to administrative and even criminal sanctions